Effect of coating type on the mechanical performance of warp-knitted fabrics and cement-based composites. (August 2018) - Quadflieg, Till; Leimbrink, Sebastian; Gries, Thomas; Stolyarov, Oleg
High-performance textiles are used for reinforcing concrete structural parts. This paper presents a technique for producing coated weft-inserted warp-knitted fabrics for concrete applications. Three types of reinforced fabrics differing in coating type and composed of alkali-resistant-glass rovings resulting in a cement composite matrix were produced. The investigated coatings include potassium silicate, carboxylated styrene butadiene rubber and epoxide. The mechanical properties of the developed fabrics and cement composites were determined according to the coating type. Thereafter, the mechanical performance of the warp-knitted reinforced fabrics was investigated using tensile tests. Finally, the properties of the composites were examined according to the coating type using a four-point bending test. The results of the characterization of the coated weft-inserted warp-knitted reinforced fabrics and cement composites based on them are presented and discussed. It is shown that the coating material has high influence on the composite properties. Samples with potassium silicate showed highest strength at the limit of proportionality, while samples with epoxide showed the highest flexural strength.